2017
DOI: 10.1016/j.bpj.2017.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV-1 gp41-Derived Virucidal Peptides on Virus-like Lipid Membranes

Abstract: Membrane fusion induced by the envelope glycoprotein enables the intracellular replication of HIV-1; hence, this process constitutes a major target for antiretroviral compounds. It has been proposed that peptides having propensity to interact with membrane interfaces might exert broad antiviral activity against enveloped viruses. To test this hypothesis, in this contribution we have analyzed the antiviral effects of peptides derived from the membrane-proximal external region and the transmembrane domain of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The virucidal effect was the strongest activity observed for RcP which might suggest that an anti-CHIKV mechanism of action for this complex might be related to a direct action on the viral particle envelope. Previous studies have shown that the virucidal effect of several compounds is closely related to an action on the virus envelope (Tang et al, 1990;Schuhmacher et al, 2003;Carravilla et al, 2017;Kong et al, 2019;Russo et al, 2019). This suggests the existence of interactions between CHIKV envelope glycoproteins and RcP.…”
Section: Discussionmentioning
confidence: 93%
“…The virucidal effect was the strongest activity observed for RcP which might suggest that an anti-CHIKV mechanism of action for this complex might be related to a direct action on the viral particle envelope. Previous studies have shown that the virucidal effect of several compounds is closely related to an action on the virus envelope (Tang et al, 1990;Schuhmacher et al, 2003;Carravilla et al, 2017;Kong et al, 2019;Russo et al, 2019). This suggests the existence of interactions between CHIKV envelope glycoproteins and RcP.…”
Section: Discussionmentioning
confidence: 93%
“…14 Thus, we next performed twophoton fluorescence imaging of Laurdan-stained GUVs to quantitatively determine lipid packing in the liposome-based vaccines that contained different amounts of Chol. 24,47 The emission spectrum of Laurdan changes in response to polarity. In a membrane context, changes in polarity are ascribed to differences in lipid packing, which influences water accessibility.…”
Section: ■ Resultsmentioning
confidence: 99%
“…GP values were calculated using in-house developed software based on MATLAB (MathWorks, MA, USA) as described in our previous papers. 24,65 After smoothing the images with a 2-pixel averaging circular filter and thresholding the intensity, GP values were calculated for every pixel on the image following eq 2,…”
Section: Functional Characterization Of Fab 10e8 and Itsmentioning
confidence: 99%
“…With 50% cholesterol, IWYIK was found to decrease the bilayer repeat distance, while LWYIK increased it [106]. There is evidence that longer peptides containing LWYIK may act as inhibitors of HIV fusion activity [107]. It was found that deletion of LWYIK from the gp41 fusion protein resulted in a fusion inactive virus [108] ; however, this study provided evidence that this segment was needed for the enlargement of fusion pores and for post-fusion activity, rather than for interaction with cholesterol and rafts.…”
Section: Role Of Cholesterol In Membrane Fusionmentioning
confidence: 97%